Identifikasi Kesalahan Siswa dalam Menyelesaikan Soal-soal Operasi Bentuk Aljabar Di kelas VIII MTs N Siabu - Syahmi, Ayi; Amir, Almira (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2017)
The background of the problem in this study is the students 'mistakes in solving mathematical questions of Algebraic material which are seen from the results of tests, interviews and the percentage of students' mistakes in solving operational problems in Algebra form.Based on the background of the research above, the purpose of this study is to find out the mistakes of students in solving the operational problems of algebraic form and the factors that influence students' mistakes in solving the algebraic forms of operating questions in class VIII MTsN Siabu.This research was conducted at MTsN Siabu. Data analysis was carried out in the form of descriptive qualitative analysis, namely analyzing and presenting facts systematically. The technique used to collect data is tests and interviews. Furthermore, this study has primary data sources, namely class VIII MTsN Siabu and secondary data sources, namely the teacher of mathematics study class VIII MTsN Siabu.The results of this study are the types of mistakes made by students in solving operating problems algebraic forms are strategy errors, translation errors, conceptual errors, calculation errors, and sign errors. Then the causes of errors made by students in completing algebraic forms of operating questions are internal factors and external factors.